Percepção de atletas sobre os apoios sociais ofertados para prática do rugby em cadeira de rodas - Guevara Becerra, Marco Antônio (2018)
The literature has attested the relevance and influence of the supports for the promotion of human development in its different dimensions. "Social support" means all strategies and tools, adaptations of participation in public and private programs, activities and resources that have been offered to people in their different contexts throughout their social, educational and personal formation. The Support Networks (SN) have an important role to favor the development of the people. The present qualtiative research aimed to describe and analyze the perception of athletes with physical disabilities on the multiple supports received and offered for the practice of Rugby in Wheelchair. Ten semi-structured interviews of wheelchair rugby players (RCR) were analyzed on the effects of the support offered by people, services and programs for the practice of the sport in order to apprehend the perception of each participant. The data were analyzed identifying nuclei of questions present in the interviews with focus on the supports and their perception. The results indicate that the most mentioned and cited support as most important to the practice of sports were from the family context; father, mother and family members. In the sporting context, the athletes highlight the support provided by clubs, teams, staffs, coaches, team, with appreciation for the training space, offer of academy, availability of professional technicians and staff support. The athletes emphasized the importance of the support offered by specialized and qualified professionals to promote their participation in the sport. Other contexts cited by athletes as sources favoring access to RCR practice were clinical context and the context of health. The athletes mentioned the government support coming from the ministerial program entitled, Bolsa Athleta. Informational support and support of infrastructural nature were highly valued.The main motivations for the practice of sports are predominantly in the field of personal desire: improvement of health, promotion of quality of life, the search for better physical conditions and the desire to rehabilitate. Athletes assess that the obstacles to RCR practice focus on financial support and the lack of sports and social infrastructure not provided by government contexts. From the results are discussed the networks of support offered for the practice of RCR, its importance and effects on people's lives. It is believed that the identification of support networks, their connections and the identification of their effects in the different life contexts of people with disabilities can provide subsidies for public policies.